Analysis of Pain and Analgesia Protocols in Acute Cerulein-Induced Pancreatitis in Male C57BL/6 Mice - Durst, Mattea; Graf, Theresia Reding; Graf, Rolf; Kron, Mareike; Arras, Margarete; Zechner, Dietmar; Palme, Rupert; Talbot, Steven R.; Jirkof, Paulin (Frontiers in Physiology, 2021)
Pancreatitis is known to be painful in humans and companion animals. However, the extent of pain in experimental mouse models of acute pancreatitis is unknown. Consequently, the severity classification of acute pancreatitis in mice is controversially discussed and standardized pain management is missing. In this study, we investigated acute Cerulein-induced pancreatitis with pain-specific and well-being orientated parameters to detect its impact on mice. Male C57BL/6J male mice were injected with Cerulein; animals that received saline injections served as control group. The animals were observed for weight change and water intake. To assess pain, behaviors like stretch-and-press and reduced rearing, the Mouse Grimace Scale, and von Frey hypersensitivity were assessed. Fecal corticosterone metabolites and burrowing behavior were assessed to detect changes in the animal’s well-being. Pancreatitis severity was evaluated with amylase and lipase in the blood and pancreas histology. To investigate whether different analgesics can alleviate signs of pain, and if they influence pancreas inflammation, animals received Buprenorphine, Paracetamol in combination with Tramadol, or Metamizole in the drinking water. The calculated intake of these analgesics via drinking reached values stated to be efficient for pain alleviation. While pancreatitis did not seem to be painful, we detected acute pain from Cerulein injections that could not be alleviated by analgesics. The number of inflammatory cells in the pancreas did not differ with the analgesic administered. In conclusion: (1) Cerulein injections appear to be acutely painful but pain could not be alleviated by the tested analgesics, (2) acute pancreatitis induced by our protocol did not induce obvious signs of pain, (3) analgesic substances had no detectable influence on inflammation. Nevertheless, protocols inducing more severe or even chronic pancreatitis might evoke more pain and analgesic treatment might become imperative. Considering our results, we recommend the use of Buprenorphine via drinking water in these protocols. Further studies to search for efficient analgesics that can alleviate the acute pain induced by Cerulein injections are needed.